HUKUMAN PEMBUNUHAN DALAM HUKUM PIDANA ISLAM DI ERA MODERN - Rokhmadi Rokhmadi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2016)
Murder in the Islamic criminal law including jarimah qishas-diyat, namely jarimah punishable by qishas (punishment commensurate/proportional) or punishment diyat (fines/restitution), the specified limits his sentence, but is categorized as a right adami (human/individual), in which the victim or his family can forgive the perpetrators, so that the penalty (qishas-diyat) can remove altogether, because in qishas no entitlements for victims' families to act as